Numerical Study of the Impact of Urban Terrain on the Loads and Performance of a Small Vertical Axis Wind Turbine. Issue 4 (September 2020) - Zamre, Pradip; Dessoky, Amgad; Grün, Maximilian von der; Lutz, Thorsten; Krämer, Ewald
Abstract: In the present study, the performance of a small vertical axis wind turbine (VAWT) is investigated in realistic urban terrain, in presence of large buildings, hill and forested area. Normally, accelerated wind can be observed on the roof-top of the high-rise buildings. Thereby, different factors such as the orography, vegetation and presence of the buildings at the site etc. influence the inflow conditions strongly and subsequently the performance and loads of wind turbines. Due to the continuously varying inflow direction, inclination and highly turbulent nature of the wind, a detailed analysis of the flow field around the building is required. A two-stages approach is preferred to reduce complexity of the problem. In the first part, the inflow conditions are investigated in the large domain by means of CFD and in the second part, performance and loads of the roof-top mounted small VAWT are investigated.